Art, City and Social Bonding: Street Gallery - Cankaya, İpek (SAUC - Street Art and Urban Creativity (repository), 2021)
Abstract: This work is a discussion on the impact, challenges and ambiguities of artists and makers presence in a community. The purpose is to raise questions on levels of possible, realistic community engagement from passers-by, active makers and sharing partners in the formation of spontaneous, enhanced identity in local neighbourhoods. The art in the street as by-product of care and meaningful engagement, without strong labels or pre-designed, carrier motivated collaborations between artists and communities is in the focus. The case study is the Flagpoles Project (1986 – 1991) initiated by Slobodan Dan Paich which consists of a great number of semi-permanent sculptures built for and with residents of the Golden Gate, Oakland, USA. Reflecting on Flagpoles Project enables this paper to re-ask the artist’s role in a community setting, and how do the artistic sensibilities, vision and cohesive visual language remain while the creative process is shared with community. The paper also focuses on an enquiry on the ambiguities on how a public art project can create a positive impact on diverse segments of a difficult neighbourhood and how can bonding through art transform the experience of public space in urban context. In general, the methodology starts from expressive inception, community context and its development. In this example it is based on interviews, testimonials, also on printed and digital materials concluding with related literature about social inclusion and role of the art in everyday setting.